2021
DOI: 10.3389/fpsyg.2021.712901
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Reading Comprehension in Higher Education: Systematic Review and Meta-Analysis

Abstract: Higher education aims for university students to produce knowledge from the critical reflection of scientific texts. Therefore, it is necessary to develop a deep mental representation of written information. The objective of this research was to determine through a systematic review and meta-analysis the proportion of university students who have an optimal performance at each level of reading comprehension. Systematic review of empirical studies has been limited from 2010 to March 2021 using the Web of Scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
1
8
0
1
Order By: Relevance
“…They needed to learn through multimedia, such as textbooks, printed materials, electronic learning sources, computer-assisted instruction, and audio and video cassettes. This was in accordance with the finding of Keawchuer (2014) which found that knowledge, skills and attitude had great impact on learning; and UNESCO (united nations educational, scientific and cultural organzation) publication (2009, as cited in de-la-Peña and Luque-Rojas, 2021) which claimed that high reading comprehension skills facilitated learning. The students with high reading comprehension skills enjoy reading and consequently improve their learning readiness.…”
Section: Discussionsupporting
confidence: 89%
“…They needed to learn through multimedia, such as textbooks, printed materials, electronic learning sources, computer-assisted instruction, and audio and video cassettes. This was in accordance with the finding of Keawchuer (2014) which found that knowledge, skills and attitude had great impact on learning; and UNESCO (united nations educational, scientific and cultural organzation) publication (2009, as cited in de-la-Peña and Luque-Rojas, 2021) which claimed that high reading comprehension skills facilitated learning. The students with high reading comprehension skills enjoy reading and consequently improve their learning readiness.…”
Section: Discussionsupporting
confidence: 89%
“…To the best of our knowledge a comprehensive study of Flesh Kincaid readability and lexical density of school Science and Social Studies textbooks has not been performed. Fang et al (2006) examined indices of lexical density in the 3rd, 5th, and 10th grades textbooks of different subjects: it was registered as 51% in the fable studied in the 3rd grade, 53% -in the 5th grade Science texts, and 59% -in the 10th grade History texts. Two studies on lexical density progress were performed on Indonesian English textbooks used in junior high school (7th, 8th, and 9th grades) (Mulyanti and Soeharto, 2020) and senior high school (10th, 11th, and 12th grades) (Putra and Lukmana, 2017).…”
Section: Lexical Densitymentioning
confidence: 99%
“…The growing number of studies on text complexity published worldwide, has not exhausted the topic even for the English language (Solnyshkina, Solovyev, Gafiyatova, Martynova, 2022) extent lexical density affects complexity of English academic texts thus testing the wellknown belief that lexical density predicts text complexity (Daller, Van Hout and Treffers-Daller, 2003) Guiraud's Index (Giroud, 1954), Corrected TTR (Carroll, 1964), Index of Herdan (Herdan, 1960, 1964), Maas (Maas, 1972, Tweedie and Baayen, 1998, Treffers-Daller, 2013; U Notational variant of Maas (Dugast, 1978;1979), D score (Malvern, Richards, 1997)…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the level of education is positively correlated with the individual's cognitive level and knowledge learning ability [e.g., (35)(36)(37)]. The higher the level of education, the easier it is to accept the technical products represented by digitization.…”
Section: Producer Knowledge Level (Produ_edu) and Consumer Knowledge Level (Consu_edu)mentioning
confidence: 99%